How Molecular and Ancillary Tests Can Help in Challenging Cytopathology Cases: Insights from the International Molecular Cytopathology Meeting - Elena Vigliar; Claudio Bellevicine; Gennaro Acanfora; Allan Argueta Morales; Anna Maria Carillo; Domenico Cozzolino; Mariantonia Nacchio; Caterina De Luca; Pasquale Pisapia; Maria D. Lozano; Sinchita Roy-Chowdhuri; Giancarlo Troncone (MDPI AG, 2024)
Over the past decade, molecular cytopathology has emerged as a relevant area of modern pathology. Notably, in patients with advanced-stage cancer, cytological samples could be the only material available for diagnosis and molecular biomarker testing to identify patients suitable for targeted therapies. As a result, the contemporary cytopathologist's role extends beyond morphological assessments to include critical skills such as evaluating the adequacy of the cytological samples and managing these specimens for molecular testing. This case collection can be a valuable source of insight, especially for young pathologists, who should learn to combine the opportunities offered by molecular biology with the basis of morphological evaluation.